THE EFL STUDENTS’ CHALLENGE AND PROBLEM ON SPEAKING ACTIVITIES DURING ONLINE LEARNING - Rizky Annisa (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2022)
Abstract: The purpose of this research was to investigate the EFL students’ challenges on speaking activities during online learning and EFL students’ problems on speaking activities during online learning. The data were collected by qualitative method within questionnaire and interview. The data were collected by online within questionnaire and interview. From the data investigation, students have many challenges on speaking activities during online learning, most of students felt there is no motivation, less understanding and lack of self-confidence. Then, students also faced several problems on speaking activities there were internet network, students’ devices, online learning environment, less interaction and limited time. As a result, online learning is not effective for speaking activities.Keywords : EFL students’ challenge, EFL students’ problem, Speaking activities, Online learning